Creative collaboration: innovation and creativity in teams - Fisher, Colin M. (Henry Stewart Talks, 2013)
What is creativity?, What promotes and inhibits creativity in organizations?, Why use teams?, Managing team processes, Compositional and improvisational creativity, Getting help for creative teams
Reviewed at 2020/11/30